Creating a Positive Work Environment: University Administration’s Responsibilities Towards Academic Staff Well-being - AMBALI, Suleiman Folorunsho (Ilorin Journal of Education, 2025)
This paper explores the critical role of university administration in fostering a positive work environment to enhance the well-being of academic staff in Nigerian higher education institutions. Against the backdrop of increasing global academic pressures and the multifaceted responsibilities of faculty, the study underscores the strategic and moral imperatives of prioritizing academic staff welfare. Drawing on empirical evidence and institutional experience, the paper outlines key dimensions of academic staff well-being—including physical, mental, professional, and financial health—and demonstrates how these factors directly impact teaching quality, research productivity, and student outcomes. It identifies systemic challenges such as inadequate funding, infrastructure deficits, excessive workloads, and rigid bureaucracies that hinder well-being in Nigerian universities. Furthermore, the paper proposes administrative strategies including participatory governance, transparent promotion systems, targeted staff development, infrastructure upgrades, and institutional culture reforms. Emphasizing long-term sustainability, it advocates for strategic planning, technology integration, partnership development, and succession planning to institutionalize well-being initiatives. Ultimately, the study concludes that investing in academic staff well-being is essential for institutional excellence, resilience, and the advancement of national higher education goals.